Effect of cement content and recycled rubber particle size on the performance of rubber-modified concrete. Issue 3 (4th May 2019) - Stallings, Katelyn A.; Durham, Stephan A.; Chorzepa, Mi G.
ABSTRACT: According to the Rubber Manufacturer's Association, the United States generated 3664 thousand metric tons of scrap tires in 2015. While most waste tires are repurposed, approximately 409.5 thousand metric tons were disposed in landfills. This study investigates an alternative use of the waste tires as a replacement of natural aggregates in concrete mixtures. This study investigated fresh concrete properties and compressive strength. Different coarse and fine aggregate rubber particle sizes were evaluated: 19-mm tire chips (TCs) and 30-mesh crumb rubber (CR). TCs were used to replace coarse aggregates, while CR was used to replace fine aggregate in the concrete mixtures in increments of 10% by volume. Concrete strength loss was reduced with a fine aggregate replacement with CR as opposed to greater losses of strength exhibited by a coarse aggregate replacement with TCs. Adequate strengths were achieved at replacement levels as high as 40% by volume with CR, whereas satisfactory strengths were achieved with only a 10% replacement of coarse aggregates with TCs. Acceptable strengths were obtained from mixtures utilizing a combination of the two rubber sizes. Cement content was observed to have greater influence on rubberized concrete compressive strength at lower rubber contents than higher levels.